Dreaming of Leaving the Nest? Immigration Status and the Living Arrangements of DACAmented - Rania Gihleb; Osea Giuntella; Jakub Lonsky (Institute of Labor Economics (IZA), 2021)
This study investigates the effects of the Deferred Action for Childhood Arrivals (DACA) on the living arrangements and housing behavior of undocumented immigrants in the U.S. Using an event-study approach and difference-in-differences (DID) estimates, we compare immigrants above and below eligibility cutoffs and demonstrate that after the adoption of the policy in June 2012, DACA-eligible immigrants were less likely to live with their parents or in multigenerational households (-11%) and more likely to live independently (+15.5%). We also reveal that DACA-eligible immigrants were less likely to live in the same house (+2%) and more likely to move out of ethnic enclaves (-3%). Lower rental costs (-4.5%) may have facilitated this transition into adulthood and the observed trends in living arrangements. DACA also led to a decline in marriage rates among DACA-eligible individuals, while we found no evidence of significant effects on cohabitation, divorce, and intermarriage. We also found no evidence of a clear impact on fertility.
Keywords: J1; J23; J24; R2; 330; immigration status; DACA; living arrangements; rental markets